Micro‐CT guided illustration of the head anatomy of penguins (Aves: Sphenisciformes: Spheniscidae). (14th April 2022) - Hadden, Peter W.; Ober, William C.; Gerneke, Dane A.; Thomas, Daniel; Scadeng, Miriam; McGhee, Charles N. J.; Zhang, Jie
Abstract: The illustration is an important tool to aid in the description and understanding of anatomy, and penguins (Aves: Sphenisciformes: Spheniscidae) are an important clade in environmental monitoring, paleontology, and other research fields. Traditionally, anatomic illustration has been informed by dissection. More recently, micro‐computed tomography (micro‐CT) has proven to be a powerful tool for three‐dimensional anatomic imaging, although larger specimens are more challenging to image due to increased X‐ray attenuation. Here, we used traditional dissection and micro‐CT to illustrate the skulls of Aptenodytes patagonicus, Eudyptula minor, and Pygoscelis papua, and the extracranial soft tissue of E. minor . Micro‐CT prevented the loss of orientation, disarticulation, and distortion of bones that might result from cleaning and drying skulls, while immobilization was achieved by freezing the specimens before imaging. All bony elements in the head were accurately depicted. Fixing, dehydrating, and diffusion staining with iodine (diceCT) enabled the identification of muscles and other large nonmineralized structures, but specimen preparation precluded the ability to show smaller nerves and vessels. The results presented here provide a guide for anatomic studies of penguins and our summary of sample preparation and imaging techniques are applicable for studies of other similarly sized biological specimens. Abstract : This illustration is a composite left lateral view of the deeper muscles of the head of a little penguin ( Eudyptula minor ) and a micro‐computed tomography image of the skull from which the bony elements were drawn, demonstrating the usefulness of traditional illustration, informed by more modern methods as well as dissection, in understanding the anatomy of the penguin head.